Coral-based climate records from tropical South Atlantic: 2009/2010 ENSO event in C and O isotopes from Porites corals (Rocas Atoll, Brazil) - Natan S. Pereira; Alcídes N. Sial; Ruy K.P. Kikuchi; Valderez P. Ferreira; Clemens V. Ullmann; Robert Frei; Adriana M.C. Cunha (Anais da Academia Brasileira de Ciências, 2015)
ABSTRACT Coral skeletons contain records of past environmental conditions due to their long life span and well calibrated geochemical signatures. C and O isotope records of corals are especially interesting, because they can highlight multidecadal variability of local climate conditions beyond the instrumental record, with high fidelity and sub-annual resolution. Although, in order to get an optimal geochemical signal in coral skeleton, sampling strategies must be followed. Here we report one of the first coral-based isotopic record from the Equatorial South Atlantic from two colonies of Porites astreoides from the Rocas Atoll (offshore Brazil), a new location for climate reconstruction. We present time series of isotopic variation from profiles along the corallite valley of one colony and the apex of the corallite fan of the other colony. Significant differences in the isotopic values between the two colonies are observed, yet both record the 2009/2010 El Niño event - a period of widespread coral bleaching - as anomalously negative δ18O values (up to −1 permil). δ13C is found to be measurably affected by the El Niño event in one colony, by more positive values (+0.39 ‰), and together with a bloom of endolithic algae, may indicate physiological alteration of this colony. Our findings indicate that corals from the Rocas Atoll can be used for monitoring climate oscillations in the tropical South Atlantic Ocean.